Pendekatan Interpretasi Teologis Kitab Suci dan Prasuposisi-Prasuposisi Teologis di Baliknya - Margaret, Carmia (Sekolah Tinggi Teologi SAAT, 2019)
Theological Interpretation of the Scripture and Theological Presuppositions Behind It. There are plenty of figures and writings that attempt to introduce, discuss, and show the workings of Theological Interpretation of Scripture (TIS) as an approach in reading the Holy Scripture; however, not many that actually dissect the theological-philosophical thoughts laid behind it. This paper will discuss the nature, essence, and characteristics of the TIS approach through some of the forming convictions behind it, which can be said as